Construcción de ciudad : entre los filos de la memoria y la violencia. Caso Manrique, Medellín (2014)
ABSTRACT: This article seeks to contribute to the recent history of Medellin (1980-2010), by reconstructing the memory of settlers of La Cruz, Bello Oriente and La Honda neighborhoods, located in the notheastern side of the city. By applying participatory methodologies on different population groups, the data obtained allow to identify significant data on memorable events that refer to processes of urbanization in these neighborhoods that are an integral part of Medellin´s popular habitat. The data points to four elements in the construction of memory: organization processes, the construction of infrastructure, the access to public services and the expression of multiple forms of violence. This article offers an interpretative description of violence and resistance seen as subjective experiences that contribute in the construction of social practices that have been central in the life histories of the inhabitants and in the configuration of territory.